Noise levels of dental equipment used in dental college of Damascus University - Mhd. Loutify Qsaibati; Ousama Ibrahim (Wolters Kluwer Medknow Publications, 2014)
Background: In dental practical classes, the acoustic environment is characterized by high noise levels in relation to other teaching areas. The aims of this study were to measure noise levels produced during the different dental learning clinics, by equipments used in dental learning areas under different working conditions and by used and brand new handpieces under different working conditions. Materials and Methods: The noise levels were measured by using a noise level meter with a microphone, which was placed at a distance of 15 cm from a main noise source in pre-clinical and clinical areas. In laboratories, the microphone was placed at a distance of 15 cm and another reading was taken 2 m away. Noise levels of dental learning clinics were measured by placing noise level meter at clinic center. The data were collected, tabulated and statistically analyzed using t-tests. Significance level was set at 5%. Results: In dental clinics, the highest noise was produced by micro motor handpiece while cutting on acrylic (92.2 dB) and lowest noise (51.7 dB) was created by ultrasonic scaler without suction pump. The highest noise in laboratories was caused by sandblaster (96 dB at a distance of 15 cm) and lowest noise by stone trimmer when only turned on (61.8 dB at a distance of 2 m). There was significant differences in noise levels of the equipment's used in dental laboratories and dental learning clinics (P = 0.007). The highest noise level recorded in clinics was at pedodontic clinic (67.37 dB). Conclusions: Noise levels detected in this study were considered to be close to the limit of risk of hearing loss 85 dB.